A study of the influence of employee empowerment on organizational citizenship behaviours of teachers within Grahamstown independent senior schools - Johnston, Dean Allan (Rhodes University, Faculty of Commerce, Rhodes Business School, 2016)
This research investigates the influence of empowerment on organisational citizenship behaviours (OCB) of teachers within Independent Senior schools in Grahamstown. Teachers, as a schools driving force, contribute immensely to the education of its students as well as determine the success and effectiveness of the school as an educational institution. The nature of a teacher's work, and indirectly the principal's job of managing these teachers, is complex and difficult to define as there are only certain behaviours which can be contractually obliged from teachers. Further behaviours which are beneficial to the organisation, such as OCB, need to be induced via incentives or encouraged via certain behavioural management initiatives, such as increased levels of empowerment. It is important for schools to encourage their teachers to participate in such beneficial behaviours as not all behaviours can be dictated or managed through contractual limitations. Previous studies and literature reviewed suggest that OCB is an important variable that significantly influences a schools performance. Such studies and literature suggest that empowerment could induce greater levels of OCB. The concepts of OCB and empowerment are defined and discussed and a 58 item Questionnaire is formulated based on the two concepts, drawn mainly from Short and Rinehart (1992) and Bogler and Somech (2004). The Questionnaire is divided into two parts, firstly OCB and secondly empowerment. Each section of the Questionnaire is divided into the relevant categories and dimensions as prescribed by past literature. The first part determines the behaviours which the participants believe form part of a teachers 'in-role' behaviour, therefore also determines which behaviours the participants believe are 'extra-role' or OCB. The second part determines the participant's perception of their empowerment in their own workplace. This research makes use of an online Questionnaire. The data is collected and described using averages, modes and medians. This data is organised in a manner which further allows for a Pearson correlation analysis test to be run. This test is used to establish the correlation relationship between the two variables in this research and the statistical significance of this relationship is analysed by observing the respective p-value. The conclusion is drawn that there exists four statistically significant positively correlated relationships between the empowerment dimension (decision making, status, self-efficacy and impact) and OCB. However there exists a weak positively correlated non-statistically significant relationship between empowerment and OCB. This suggests that empowerment as a whole does not greatly influence higher levels of OCB, however the four individual dimensions of empowerment do have a positive influence.
Keywords: Uncatalogued